Prenatal Diagnosis, Neonatal Outcomes, and Management of Pregnancies Complicated by Gastroschisis - Rajuddin, Rajuddin; Meutia, Inong Indira (CoinReads Media Prima, 2025)
Introduction: Gastroschisis, a congenital abdominal wall defect, causes external protrusion of intestines and organs due to incomplete wall closure near the umbilicus. Accurate prenatal diagnosis through ultrasonography requires skilled operators to detect the defect and guide management. Early identification enables perinatal care planning to minimize complications, such as organ perforation, and optimize neonatal outcomes. This case report examines the prenatal diagnosis and management of gastroschisis in a primigravida, highlighting ultrasonography's role in clinical decision-making. Case Description: A 26-year-old primigravida at 34–35 weeks gestation was referred from Zubir Mahmud Regional Hospital with a prenatal diagnosis of gastroschisis. She reported severe abdominal pain and vaginal spotting for three weeks. Physical examination indicated stable hemodynamics, with obstetric findings including a fundal height of 26 cm, estimated fetal weight of 2015 g, left-sided fetal back, fetal heart rate of 142 beats/min, breech presentation, and no contractions. Speculum examination revealed a closed external cervical os, no dilation, negative fluxus, positive flour, protruding amniotic membranes, and a positive nitrazine test. Vaginal examination showed a posterior, soft cervix with no dilation or palpable fetal parts. The pregnancy was diagnosed with congenital gastroschisis, and a cesarean section was planned to prevent abdominal organ perforation. Conclusion: Gastroschisis, identified at 34–35 weeks gestation, necessitates early prenatal diagnosis to prepare for appropriate perinatal care. Cesarean delivery is a preferred strategy to reduce risks of organ damage, supporting improved neonatal outcomes in affected pregnancies.